2019
DOI: 10.1007/s00220-019-03331-9
|View full text |Cite
|
Sign up to set email alerts
|

All Weight Systems for Calabi–Yau Fourfolds from Reflexive Polyhedra

Abstract: For any given dimension d, all reflexive d-polytopes can be found (in principle) as subpolytopes of a number of maximal polyhedra that are defined in terms of (d + 1)-tuples of integers (weights), or combinations of k-tuples of weights with k < d + 1. We present the results of a complete classification of sextuples of weights pertaining to the construction of all reflexive polytopes in five dimensions. We find 322 383 760 930 such weight systems. 185 269 499 015 of them give rise directly to reflexive polytope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…The analysis of fibration structures of complete intersection Calabi-Yau fourfolds in [25] suggests that again most known constructions should lead predominantly to Calabi-Yau fourfolds that are genus one or elliptically fibered. The classification of hypersurfaces in reflexive 5D polytopes has not been completed, although the complete set of 3.2×10 11 associated weight systems has recently been constructed [49]. In fact, recent work on classifying toric threefold bases that can support elliptic Calabi-Yau fourfolds suggests that the number of such distinct bases already reaches enormous cardinality on the order of 10 3000 [50,40].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of fibration structures of complete intersection Calabi-Yau fourfolds in [25] suggests that again most known constructions should lead predominantly to Calabi-Yau fourfolds that are genus one or elliptically fibered. The classification of hypersurfaces in reflexive 5D polytopes has not been completed, although the complete set of 3.2×10 11 associated weight systems has recently been constructed [49]. In fact, recent work on classifying toric threefold bases that can support elliptic Calabi-Yau fourfolds suggests that the number of such distinct bases already reaches enormous cardinality on the order of 10 3000 [50,40].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, complete intersection Calabi-Yau d-folds of codimension m are related to nef-partitions of d + m-dimensional reflexive polytopes [61]. For recent progress on the classification of five-dimensional reflexive polytopes see [132].…”
Section: Eliptically Fibered Calabi-yau As Toric Hypersurfacesmentioning
confidence: 99%
“…For a given reflexive polytope one can systematically search for the toric fibrations of the corresponding toric variety. This has been used by [134] and [132] to scan for fibrations in the complete Kreuzer-Skarke list.…”
Section: Jhep11(2019)170mentioning
confidence: 99%
“…The largest h 1,1 for a Calabi-Yau threefold associated with a non-fibered 4D polytope comes from the case with Hodge numbers (140, 62), as previously identified in [23]. The next-largest values of h 1,1 come from polytopes associated with Calabi-Yau threefolds having Hodge numbers It is very interesting that the polytopes corresponding with large h 1,1 that do not have 2D reflexive subpolytopes have Hodge numbers h 2,1 in the narrow range 60-63; the first exception as h 1,1 decreases has the Hodge numbers (95, 55), and for all h 1,1 > 61 the non-fibered cases have h 2,1 in the range 48-65. It would be interesting to understand better whether this family of polytopes has some common structure associated with the lack of an elliptic or genus one fibration for the corresponding toric varieties.…”
Section: Fiber Analysis Of All Reflexive 4d Polytopesmentioning
confidence: 63%
“…In [54] it was shown that the fraction of CICY Calabi-Yau fourfolds that has an obvious elliptic or genus one fibration (99.95%) is even larger than the fraction of CICY Calabi-Yau threefolds with this property (99.3%). There is no complete analysis of reflexive 5D polytopes, though there are some partial results in this direction [55] and some analysis of the fibration structure of these polytopes was carried out in [26]. In fact, direct construction of toric threefold bases that support elliptic and genus one toric hypersurface Calabi-Yau fourfolds shows that the number of such bases alone is extraordinarily large, on the order of 10 3000 [48,56,57].…”
Section: Discussionmentioning
confidence: 99%